A line‐source method for aligning on‐board and other pinhole SPECT systems. Issue 12 (12th November 2013) - Yan, Susu; Bowsher, James; Yin, Fang‐Fang
Abstract : Purpose: : In order to achieve functional and molecular imaging as patients are in position for radiation therapy, a robotic multipinhole SPECT system is being developed. Alignment of the SPECT system—to the linear accelerator (LINAC) coordinate frame and to the coordinate frames of other on‐board imaging systems such as cone‐beam CT (CBCT)—is essential for target localization and image reconstruction. An alignment method that utilizes line sources and one pinhole projection is proposed and investigated to achieve this goal. Potentially, this method could also be applied to the calibration of the other pinhole SPECT systems. Methods: : An alignment model consisting of multiple alignment parameters was developed which maps line sources in three‐dimensional (3D) space to their two‐dimensional (2D) projections on the SPECT detector. In a computer‐simulation study, 3D coordinates of line‐sources were defined in a reference room coordinate frame, such as the LINAC coordinate frame. Corresponding 2D line‐source projections were generated by computer simulation that included SPECT blurring and noise effects. The Radon transform was utilized to detect angles ( α ) and offsets ( ρ ) of the line‐source projections. Alignment parameters were then estimated by a nonlinear least squares method, based on the α and ρ values and the alignment model. Alignment performance was evaluated as a function of number of line sources, Radon transform accuracy, finite line‐source width, intrinsic camera resolution, Poisson noise, and acquisition geometry. Experimental evaluations were performed using a physical line‐source phantom and a pinhole‐collimated gamma camera attached to a robot. Results: : In computer‐simulation studies, when there was no error in determining angles ( α ) and offsets ( ρ ) of the measured projections, six alignment parameters (three translational and three rotational) were estimated perfectly using three line sources. When angles ( α ) and offsets ( ρ ) were provided by the Radon transform, estimation accuracy was reduced. The estimation error was associated with rounding errors of Radon transform, finite line‐source width, Poisson noise, number of line sources, intrinsic camera resolution, and detector acquisition geometry. Statistically, the estimation accuracy was significantly improved by using four line sources rather than three and by thinner line‐source projections (obtained by better intrinsic detector resolution). With five line sources, median errors were 0.2 mm for the detector translations, 0.7 mm for the detector radius of rotation, and less than 0.5° for detector rotation, tilt, and twist. In experimental evaluations, average errors relative to a different, independent registration technique were about 1.8 mm for detector translations, 1.1 mm for the detector radius of rotation (ROR), 0.5° and 0.4° for detector rotation and tilt, respectively, and 1.2° for detector twist. Conclusions: : Alignment parameters can be estimated using one pinhole projection of line sources. Alignment errors are largely associated with limited accuracy of the Radon transform in determining angles ( α ) and offsets ( ρ ) of the line‐source projections. This alignment method may be important for multipinhole SPECT, where relative pinhole alignment may vary during rotation. For pinhole and multipinhole SPECT imaging on‐board radiation therapy machines, the method could provide alignment of SPECT coordinates with those of CBCT and the LINAC.